غلو الخوارج في الدين وتطرفهم وآثاره في العصر الحاضر) دراسة تحليلية( (Journal of Humanitarian and Applied Sciences, 2023)
The research deals with the issue of extremism and extremism in religion and their effects in the present age. And that is one of the concepts that provokes many discussions and debates among writers and researchers in this era, because the issue is linked to the meanings of other concepts, such as extremism, fundamentalism, terrorism, intellectual violence, excess and negligence, and other concepts and the bad effects that this causes on the structure, security and safety of society. What is imperative to study and diagnose this phenomenon, then try to develop effective solutions for it in light of the intellectual conflicts that most Arab and Muslim societies suffer from; As a result of the emergence of religious extremism and extremism, in a manner that tore these societies apart and made them lose their social security and family bonds.The phenomenon was found among the Hindus and the Magi, the Greeks and the Romans, the Jews and their rabbis, the Christians and their monks, and its influence passed to many Islamic sects later. Until the matter came to the point of ingenuity, and indeed some Muslims atoning for some of them, exploiting that in stirring up strife, fighting and quarreling among them, and the effects of that and their rumination among many of this era's extremists and thinkers remained under the cloak of religion, especially after a group of contemporary hardliners and scholars of the Sultan was able to Ruminating on the theory of absolute obedience to the ruler, making it the pole of conflict, and naming the Kharijites on all those who disagree with their opinion in criticizing the absolute obedience of the ruler, no matter how wrongful or corrupt the land is unlawfully, and if he kills unjustly, and if he commits adultery in public on television, it is not permissible to deny him. Accordingly, he is a misguided external, and he must be killed, abused and brought closer to God.